Students’ Experiences in Learning Language Skills - Fithriyah, Fithriyah (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
When learning a new language, students frequently face a range of challenges. To overcome these problems, they often employ multiple strategies. Variations in language learning experiences and proficiency levels can contribute to differences in the difficulties encountered and the strategies utilized by students. This study aimed to explore the weaknesses faced by students based on their language learning experiences, and the strategies they use to address these issues. Using qualitative research methods, interviews were conducted with 15 students from the English language education department. The findings reveal two primary problem areas: linguistic and psychological difficulties. Additionally, the students employed various strategies, such as self-study, regular practice, and joining campus student associations.